Therapeutic drug monitoring of beta-lactam antibiotics: influence of sample stability on the analysis of piperacillin, meropenem, ceftazidime and flucloxacillin by HPLC-UV - Pinder, Nadine; Brenner, Thorsten; Swoboda, Stefanie; Weigand, Markus A.; Hoppe-Tichy, Torsten (Journal of pharmaceutical and biomedical analysis, 2017)
Introduction Therapeutic drug monitoring (TDM) is a useful tool to optimize antibiotic therapy. Increasing interest in alternative dosing strategies of beta-lactam antibiotics, e.g. continuous or prolonged infusion, require a feasible analytical method for quantification of these antimicrobial agents. However, pre-analytical issues including sample handling and stability are to be considered to provide valuable analytical results. Methods for the simultaneous determination of piperacillin, meropenem, ceftazidime and flucloxacillin, a high performance liquid chromatography (HPLC) method including protein precipitation was established utilizing ertapenem as internal standard. Long-term stability of stock solutions and plasma samples were monitored. Furthermore, whole blood stability of the analytes in heparinized blood tubes was investigated comparing storage under ambient conditions and 2-8°C. Results A calibration range of 5-200μg/ml (piperacillin, ceftazidime, flucloxacillin) and 2-200μg/ml (meropenem) was linear with r2>0.999, precision and inaccuracy were <9% and <11%, respectively. The successfully validated HPLC assay was applied to clinical samples and stability investigations. At −80°C, plasma samples were stable for 9 months (piperacillin, meropenem) or 13 months (ceftazidime, flucloxacillin). Concentrations of the four beta-lactam antibiotics in whole blood tubes were found to remain within specifications for 8h when stored at 2-8°C but not at room temperature. Conclusions The presented method is a rapid and simple option for routine TDM of piperacillin, meropenem, ceftazidime and flucloxacillin. Whereas long-term storage of beta-lactam samples at −80°C is possible for at least 9 months, whole blood tubes are recommended to be kept refrigerated until analysis.